Correlation of N-terminal fragments of Atrial Natriuretic Neuropeptides (NT-ProANP) with Left Ventricle Ejection Fraction in Cases with Acute Myocardial Infarction - Hemid Al-Athari, Ali (Journal of Biomedicine and Biochemistry, 2023)
Background This study aimed to assess the correlation of natriuretic neuropeptides (NT-ProANP) with the left ventricular ejection fraction (LVEF) in patients with acute myocardial (AMI).Materials and Methods This case-control study composed of 120 pa- tients was recruited from the cardiac center in Babylon, Iraq. The plasma levels of NT-ProANP and echocardiographic measure of the left ventricle ejection fraction percentage (LVEF%) for both patients and controls as well as demographic data were taken.Results The mean ages were 61.9 ± 13.2 and 33.1 ± 8.3 years for pa- tients and control, respectively, 80.8% of the candidates were male. The differences in NT-ProANP serum levels between AMI patients and con- trols were highly significant p-0.001. There was a good diagnostic ability of NT-ProANP to predict patients with AMI from the healthy subjects by ROC-curve analysis: AUC=0.957, sensitivity=0.961, specificity=0.962, 95%CI=0.927 – 0.987, and p>0.05. Whereas, there was a poor diagnostic performance of NT-ProANP to predict LVEF%: AUC=0.438, sensitiv- ity=0.438, specificity=0.519, 95%CI=0.285 – 0.598, and p>0.05. Serum concentrations of NT-ProANP showed no significant correlation with the measures of left ventricular EF%, age, and BMI among AMI patients. The serum levels of NT-ProANP revealed no significant variations between AMI patients with low and those with preserved LV functionsConclusion The study suggests that the measurement of NT-ProANP was not correlated to LVEF%, although its levels were significantly higher among patients with AMI compared to the healthy controls.